Skeletal muscle memory: implications for sports, aging and nutrition - Pérez-Castillo, Íñigo M.; Ruiz-Caride, Sergio R.; Rueda, Ricardo; López-Chicharro, José; Segura-Ortiz, Felipe; Bouzamondo, Hakim (Frontiers in Nutrition, 2025)
Observations of an enhanced hypertrophic response in previously trained muscles following periods of detraining have led researchers to propose that muscle tissue retains a form of “cellular memory”, even after returning to baseline muscle mass. Recent advances in research methodologies have enabled deeper investigation into the underlying mechanisms, with myonuclear permanence emerging as a potential candidate. While intracellular signaling pathways that mediate anabolic stimuli and promote translational efficiency have been extensively studied, the role of transcriptional output, governed by the number of myonuclei, remains comparatively underexplored. A solid body of evidence in humans supports the need for satellite cell-mediated myonuclear accretion to achieve muscle growth that exceeds the transcriptional limits of existing myonuclei. However, it remains unclear whether accrued myonuclei persist indefinitely or are eventually removed, and the mechanisms governing their potential removal remain speculative. Notably, aging populations may not only exhibit diminished capacity to recruit satellite cells but also potentially reduced ability to retain myonuclei, which may be linked to age-related muscle wasting. Training exercise combined with nutritional strategies leveraged by athletes, including protein/amino acid intake, polyphenol-rich ingredients, and different ergogenic compounds such as creatine, might be beneficial to promote satellite cell responses and myonuclear accretion in situations where muscle mass regain and maintenance are purposed, such as injury recovery and aging.